ChemInform Abstract: Double C—H Amination by Consecutive SET Oxidations. Issue 40 (September 2016) - Evoniuk, Christopher J.; Hill, Sean P.; Hanson, Kenneth; Alabugin, Igor V.
Abstract: The intramolecular C—H amination of amines (I) and (VII) proceeds readily in the presence of DDQ as oxidant and FeCl3 as catalyst leading to substituted quinolines (II) and phenanthridines (VIII), respectively.